Strengthening the Gyeongsangbuk–West Java Sister Province Relationship through Cultural Exchange at the 8th Global Youth Camp - Muthi Najwa Hanifa; Windy Dermawan (International Journal of Science and Environment (IJSE), 2025)
This study analyzes the subnational cooperation between West Java Province, Indonesia, and Gyeongsangbuk-do Province, Republic of Korea, through the 8th Global Youth Camp 2025. Held on August 17–23, 2025, in collaboration with Sangji Catholic University, the event gathered youth delegates from six Asian countries to promote intercultural understanding and regional collaboration. Using a descriptive–qualitative approach, the research explores how this program reflects West Java’s paradiplomacy efforts within Indonesia’s foreign policy framework. The findings show that West Java’s participation strengthens its international presence, enhances youth capacity, and expands global partnerships while aligning with Indonesia’s public diplomacy goals. The cooperation also demonstrates how subnational diplomacy can balance national interests with regional development needs. Overall, the West Java–Gyeongsangbuk-do partnership serves as a model for effective paradiplomacy that fosters mutual growth, people-to-people connections, and sustainable international engagement